2011
DOI: 10.1111/j.1442-9071.2010.02457.x
|View full text |Cite
|
Sign up to set email alerts
|

Anti‐adenoviral effect of interferon‐β and interferon‐γ in serotypes that cause acute keratoconjunctivitis

Abstract: These results suggest that both interferon-β and interferon-γ have anti-adenoviral activity in vitro. Interferons have the potential to be used for local treatment of adenoviral keratoconjunctivitis, although further evaluation in animal models and clinical trials is necessary.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 26 publications
0
4
0
1
Order By: Relevance
“…Since IFN-α appears not to directly affect AdHu5 transgene expression 38 , it seems more likely that IFN-β is mediating this effect. In addition, human IFN-β has been described to have a detrimental effect on the replication of different adenoviral serotypes in vitro 39 .…”
Section: Discussionmentioning
confidence: 99%
“…Since IFN-α appears not to directly affect AdHu5 transgene expression 38 , it seems more likely that IFN-β is mediating this effect. In addition, human IFN-β has been described to have a detrimental effect on the replication of different adenoviral serotypes in vitro 39 .…”
Section: Discussionmentioning
confidence: 99%
“…No specific antiviral drugs are currently available for the treatment of EKC or any other infection caused by adenoviruses. Interestingly, it has been suggested that five strains of different serotypes of adenovirus, types 3 (AdV3; species B), 4 (species E), 8, 19a and 37 (species D) involved in acute keratoconjunctivitis are highly inhibited by IFN-b and IFN-g in the A549 cell line, [2] However, IFN therapy in adenoviral keratoconjunctivitis has not been evaluated in clinical trials yet.…”
Section: Novel Therapies In Infectious Keratoconjunctivitis 21 Intementioning
confidence: 99%
“…Adenovirus vaccines are not used due to their proven oncogenicity [19]. In vitro studies on models of different viruses have shown the antiviral effect of natural interferons, as well as immunoglobulin G [20]. In this regard, the use of drugs that activate non-specific immune response factors and thus increase the body's overall resistance may be appropriate for the treatment and prevention of SARS [20][21][22].…”
mentioning
confidence: 99%
“…In vitro studies on models of different viruses have shown the antiviral effect of natural interferons, as well as immunoglobulin G [20]. In this regard, the use of drugs that activate non-specific immune response factors and thus increase the body's overall resistance may be appropriate for the treatment and prevention of SARS [20][21][22]. Drugs with immunomodulatory and so-called secondary antiviral action are widely studied [2,7,[23][24][25][26][27].…”
mentioning
confidence: 99%